Cap-assisted colonoscopy and detection of Adenomatous Polyps (CAP) study: a randomized trial - Pohl, Heiko; Bensen, Steve P.; Toor, Arifa; Gordon, Stuart R.; Levy, L. Campbell; Berk, Brian; Anderson, Peter B.; Anderson, Joseph C.; Rothstein, Richard I.; MacKenzie, Todd A.; Robertson, Douglas J. (Endoscopy, 2015)
Background and study aim: Cap-assisted colonoscopy has improved adenoma detection in some but not other studies. Most previous studies have been limited by small sample sizes and few participating endoscopists. The aim of the current study was to evaluate whether cap-assisted colonoscopy improves adenoma detection in a two-center, multi-endoscopist, randomized trial. Patients and methods: Consecutive patients who presented for an elective colonoscopy were randomized to cap-assisted colonoscopy (4-mm cap) or standard colonoscopy performed by one of 10 experienced endoscopists. Primary outcome measures were mean number of adenomas per patient and adenoma detection rate (ADR). Secondary outcomes included procedural measures and endoscopist variation; a logistic regression model was employed to examine predictors of increased detection with cap use.Results: A total of 1113 patients (64 % male, mean age 62 years) were randomized to cap-assisted (n = 561) or standard (n = 552) colonoscopy. The mean number of adenomas detected per patient in the cap-assisted and standard groups was similar (0.89 vs. 0.82; P = 0.432), as was the ADR (42 % vs. 40 %; P = 0.452). Cap-assisted colonoscopy achieved a faster cecal intubation time (4.9 vs. 5.8 minutes; P < 0.001), a similar cecal intubation rate (99 % vs. 98 %; P = 0.326), and a higher terminal ileum intubation rate (93 % vs. 89 %; P < 0.028). Cap-assisted colonoscopy resulted in a 20 % increase in ADR for some endoscopists and in a 15 % decrease for others. Individual preference for the cap was an independent predictor of increased adenoma detection in adjusted analysis (P < 0.001), whereas baseline low adenoma detection was not.Conclusion: Although the efficiency of cecal and terminal ileum intubation was slightly improved by cap-assisted colonoscopy, adenoma detection was not. Cap-assisted colonoscopy may be beneficial for selected endoscopists.Trial registration: clinicalTrials.gov (NCT01935180).